Low-dose aspirin for preventing intrauterine growth restriction and pre-eclampsia in sickle cell pregnancy (PIPSICKLE): a randomised controlled trial (study protocol) - Bosede Bukola Afolabi; Titilope Adenike Adeyemo; Ochuwa Adiketu Babah; Oluwakemi Ololade Odukoya; Obinyo Nwaiwu; Yusuf Abisowo Oshodi; Babatunde A Ogunnaike (BMJ Open)
Introduction Pregnancy in sickle cell disease is fraught with many complications including pre-eclampsia (PE) and intrauterine growth restriction (IUGR). Previously, we found an abnormality in prostacyclin–thromboxane ratio in sickle cell pregnant women, a situation that is also found in non-sickle pregnancies with PE and unexplained IUGR. Low-dose aspirin (LDA) has been shown to reduce the incidence of PE and IUGR in high-risk women by reducing the vasoconstrictor thromboxane while sparing prostacyclin, in effect ‘correcting’ the ratio. It has been found to be safe for use in pregnancy but has not been tested in sickle cell pregnancy. We hypothesise that LDA will reduce the incidence of IUGR and PE in pregnant haemoglobin SS (HbSS) and haemoglobin SC (HbSC) women.Methods and analysis This is a multisite, double blind, randomised controlled trial, comparing a daily dose of 100 mg aspirin to placebo, from 12 to 16 weeks’ gestation until 36 weeks, in Lagos state, Nigeria. Four hundred and seventy-six eligible pregnant HbSS and HbSC women will be recruited consecutively, randomly assigned to either group and followed from recruitment until delivery. The primary outcome will be the incidence of birth weight below 10th centile for gestational age on INTERGROWTH 21 birth weight charts, or incidence of miscarriage or perinatal death. Secondary outcomes will include PE, maternal death, preterm delivery, perinatal death, number of crises, need for blood transfusion and complications such as infections and placental abruption. Analysis will be by intention to treat and the main treatment effects will be quantified by relative risk with 95% CI, at a 5% significance level.Ethical approval Ethical approval has been granted by the Health Research and Ethics committees of the recruiting hospitals and the National Health Research and Ethics Committee. Study findings will be presented at conferences and published appropriately.Trail registration number PACTR202001787519553; Pre-results.